Strengthening The Role Of Social Worker In Theprotection For Vulnerable Children In Chengdu, China - Huang, Chunmei (2024)
The objectives of this study are to analyse the current situation of protecting vulnerable children, measure social workers' readiness to protect vulnerable children, assess the challenges faced by social workers in this effort, and propose a social work intervention model to enhance the protection of vulnerable children. Chengdu was chosen as the research site, and a qualitative research method was employed to interview 20 social workers. NVivo Plus 12 analysis software was used to thematically analyze the research questions. Firstly, the needs of vulnerable children encompass basic survival needs, protected needs, psychological needs, and social support needs. Most of the organizations' service funding sources originated from the government. Social workers' practices for vulnerable children include protective, relief, supportive, developmental, and advocative services. Social workers collaborate with other systems, such as the community, child directors, and other institutions. Secondly, the readiness of social workers to protect vulnerable children involves various policies and government and social work professional organizations. Additionally, it comprises social work professional advantages, service roles, professional values, professional methods, and resource linkage. Thirdly, the difficulties faced by social workers involved in the protection of vulnerable children encompass social workers' mobility and lack of capacity at the Micro-level.